1994
DOI: 10.1126/science.7973732
|View full text |Cite
|
Sign up to set email alerts
|

Lymphotactin: a Cytokine that Represents a New Class of Chemokine

Abstract: In this study, the cytokine-producing profile of progenitor T cells (pro-T cells) was determined. During screening of a complementary DNA library generated from activated mouse pro-T cells, a cytokine designated lymphotactin was discovered. Lymphotactin is similar to members of both the Cys-Cys and Cys-X-Cys chemokine families but lacks two of the four cysteine residues that are characteristic of the chemokines. Lymphotactin is also expressed in activated CD8+ T cells and CD4-CD8- T cell receptor alpha beta + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
360
1
5

Year Published

1996
1996
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 597 publications
(369 citation statements)
references
References 17 publications
3
360
1
5
Order By: Relevance
“…Two major problems still need to be solved. Firstly, although the expression of XCL1 has been described virtually in all lymphocyte populations, including CD8 ϩ lymphocytes (7)(8)(9)(10)(11)(12), CD4 ϩ lymphocytes (19 -21), NK cells (7,13,14), and ␥␦ ϩ T cells (17,18) under a variety of experimental conditions, the available data are mostly based on nonquantitative PCR analyses, and no thorough comparison of the actual XCL1 synthesis and/or the expression in different T cell populations was attempted. Secondly, although clear XCL1 effects other than lymphocyte migration were described on several cell types, including CD4 ϩ T cells (22,57), this issue is as yet incompletely addressed, and the position of XCL1 within the cytokine/ chemokine network is still elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Two major problems still need to be solved. Firstly, although the expression of XCL1 has been described virtually in all lymphocyte populations, including CD8 ϩ lymphocytes (7)(8)(9)(10)(11)(12), CD4 ϩ lymphocytes (19 -21), NK cells (7,13,14), and ␥␦ ϩ T cells (17,18) under a variety of experimental conditions, the available data are mostly based on nonquantitative PCR analyses, and no thorough comparison of the actual XCL1 synthesis and/or the expression in different T cell populations was attempted. Secondly, although clear XCL1 effects other than lymphocyte migration were described on several cell types, including CD4 ϩ T cells (22,57), this issue is as yet incompletely addressed, and the position of XCL1 within the cytokine/ chemokine network is still elusive.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Lymphotactin (Lptn) is a C chemokine that specifically regulates the migration of T cells and NK cells. [17][18][19][20] Dilloo et al 21 reported that cotransfection of Lptn and interleukin-2 (IL-2) genes into tumor tissue could induce potent antitumor immunity through an attraction-expansion approach. We have also found that Lptn gene-modified DC could deliver MHC I-restricted tumor antigen peptide more efficiently to induce antitumor immunity in the 3LL Lewis lung carcinoma model.…”
Section: Ance To Tumor Challenge Most Effectively It Was Found That mentioning
confidence: 99%
“…Ex vivo experiments have suggested that the Lptn is particularly important for the recruitment of T cells and NK cells to the site of an immune response. [17][18][19][20] Therefore, the cotransfection of Lptn and TAA gene into DC may have the potential to overcome the above limitation and may be a promising approach to improve the therapeutic efficacy of DC-based tumor vaccines. Many studies showed that DC could attract T cells by secreting chemokines.…”
Section: Gene Therapymentioning
confidence: 99%
“…Lymphotactin belongs to the chemokine group 38-40 that is regulated by proinflammatory or infectious stimuli, and was shown to be expressed mainly in activated T and Natural Killer (NK) cells. 41,42 The human Lymphotactin is implicated in allograft rejection, inflammatory bowel diseases and other immune system related diseases. 43 In general, chemokines stimulate cells of the immune system through activating specific G protein-coupled receptors (GPCRs).…”
Section: Introductionmentioning
confidence: 99%